Associations between Age-Related Changes in the Core Vestibular Projection Pathway and Balance Ability: A Diffusion Tensor Imaging Study - Sang Seok Yeo; Jung Won Kwon; In Hee Cho (Behavioural Neurology)
Objective. We investigated the changes of the vestibulospinal tract (VST) and parietoinsular vestibular cortex (PIVC) using diffusion tensor imaging (DTI) and relation to balance between old and young healthy adults. Methods. This study recruited eleven old adults (6 males, 5 females; mean age 63.36±4.25 years) and 12 young adults (7 males, 5 females; mean age 28.42±4.40 years). The lateral and medial VST and PIVC were reconstructed using DTI. Fractional anisotropy (FA), mean diffusivity (MD), and tract volume were measured. The six-minute walk test (6-MWT), the timed up and go test (TUG), and the Berg balance scale (BBS) were conducted. Spatiotemporal parameters during tandem gait and values of sway during one-leg standing using the wearable sensors were measured. All parameters between two groups were analyzed by the Mann-Whitney U test and independent t-test. Results. Statistically significant decrease in old adults was detected in the tract volume of lateral (p=0.005) and medial VST (p≤0.001) and PIVC (p=0.020). A significant decrease in FA of lateral VST (p=0.044) and MD of medial VST (p=0.001) was seen in old adults. Stride length (p=0.003) and velocity (p=0.001) during tandem gait in old adults were significantly decreased. 6MWT (p≤0.001) showed significant decrease, while TUG (p≤0.001) showed significant increase in old adults. However, mean BSS (p=0.296) was nonsignificantly different. In eyes-open condition during one-leg standing, all parameters except for reciprocal compensatory index (RCI) values were significantly decreased in old adults. The RCI in the anteroposterior (AP) direction (p≤0.001) was increased in old adults; however, the mediolateral direction (p=0.301) was nonsignificantly different between the two groups. In eye-closed condition, the changes of ankle (p=0.031) and hip (p=0.004) sway and the center of mass in the AP direction (p=0.014) showed to be significantly higher in old adults than in young adults. Conclusion. The results suggested that there was a relationship between DTI parameters in the vestibular neural pathway and balance according to aging.